Fundamental molecular biology - Allison, Lizabeth A., 1958- (Hoboken, NJ : Wiley-Blackwell, 2021)
'While there is an innate fascination and interest in how our own genes influence our lives, molecular biology students are daunted by the amount of information they need to assimilate in order to succeed in the course. And, with the fast pace of discovery in the field, it is difficult to find suitable, up to date texts for the course-they are either too advanced, comprehensive and overwhelming detailed, or they are too basic, superficial, and less experimental in their approach. Instructors find it difficult to decide what topics are the most important to include and exclude in the course when presented with an extensive array of choices. Fundamental Molecular Biology is selective in its coverage and presents essential topics that allow students to develop an understanding of how molecular biology is applied to the analysis of complex systems. Through the process of discovery-- observations, questions, experimental designs, results and conclusions-and with an emphasis on the language of molecular biology, students can focus on the key ideas they need to succeed in the course. Students will also have the support they need outside the classroom to leave your course knowing the core, fundamental concepts of molecular biology delivered through a visually engaging, and focused text with a rich media program that promotes self-study. With a strong emphasis on biomedical research and discovery, students are exposed to both classic and the most up to date techniques and research in molecular biology today. Our book encourages reading and discovery through in-text tools, and media tools'--
Includes index.
Keywords: Molecular biology -- Textbooks; Molecular Biology